RETRACTED: Development of Russian rural tourism (agrotourism) ensuring life safety - Masaleva Maria; Nabiullina Victoria (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001